On Rethinking Our Classrooms: A Critical Pedagogy View - Yolanda Samacá Bohórquez (Asociación Colombiana de Profesores de Ingles, 2012)
This paper, as its title suggests, introduces some reflections on the importance critical pedagogy as well as awareness-raising practices have in education today, especially in language teacher preparation programs, and how they provide a new opportunity for pre-service teachers to re-think their pedagogical experiences for social transformation. Critical pedagogy (CP) as a philosophy of life helps teachers achieve a better understanding of what teaching really entails and raising awareness fosters reflection regarding our practices in educational settings, starting in the language classroom, exploring on the one hand, what pre-service teachers think and perceive about teaching and learning in the context they are involved in, and on the other hand, how those perceptions might influence their educational practices.